PENGARUH KONSELING KELUARGA BERENCANA TERHADAP PENGAMBILAN KEPUTUSAN ALAT KONTRASEPSI PADA IBU NIFAS - Maya Maftuha; Desy Purnamasari; Wahyu Fuji Hariani (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKes Banyuwangi, 2022)
In Indonesia, the use of long-term contraceptive methods tends to decrease in 2018. One factor in the high high-risk pregnancy at the Kebaman Health Center, Banyuwangi is the increase in distance between children <2 years by 18.52% (2020). Postpartum mothers who are given counseling on family planning using the decision making tool will choose to use contraception tools according to their choices and needs. This study aims to determine the effect of family planning counseling on contraceptive decision making in postpartum mothers. The research method is pre-experimental with a posttest only approach with control group design. The study was conducted in the working area of ​​the Kebaman Health Center from December 2021 to January 2022 with a population of 34 postpartum mothers. Sampling used a total sampling technique of 34 respondents and divided into two groups, namely 17 respondents who received family planning counseling and 17 respondents who did not receive family planning counseling (control group). The analysis of this study used the Chi-square test. All research procedures have gone through an ethical clearance process. The results showed that 88.2% of postpartum mothers who received family planning counseling chose to use contraception and 76.5% of postpartum mothers who did not receive family planning counseling chose not to use contraceptives. The results of data analysis stated that there was an effect of family planning counseling on contraceptive decision making in postpartum mothers (p=0.000). The conclusion of this study is that family planning counseling is an important process in making contraceptive decisions. Health workers, especially midwives, are expected to always provide family planning counseling on time by using the ABPK flipchart.